Arabic Language Learning Through the Singing Method for Early Childhood - Panggabean, Muawiyah Lani; Rambe, Aisyah Putri; Afifah, Hilyatul Ulya Nazwa; Lubis, Hilda Zahra (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study investigates the effectiveness of the singing method in teaching Arabic to early childhood learners. Using a descriptive qualitative approach, data were gathered through direct field observations, interviews with practitioners, and literature reviews. The findings highlight that singing is an effective approach to introduce Arabic vocabulary to children, enhancing their ability to recall words and improving their pronunciation. Songs with simple, relatable themes, such as hijaiyah letters, numbers, and family names, facilitate language acquisition by making learning enjoyable and engaging. Additionally, the singing method fosters children's motivation and active participation in the learning process while also developing their critical thinking and creativity. However, challenges such as limited Arabic-themed songs and classroom dynamics in large groups were noted. Despite these limitations, the singing method is recommended for early childhood education due to its positive impact on linguistic and cognitive development. Teachers are encouraged to innovate by creating new songs or adapting existing ones to further improve learning outcomes.